(untitled) (City Dental College Journal, 2012)
Loss of occlusal vertical dimension is a frequently observed problem in the middle aged and aged population who intends to retain their natural dentition. This type of patient has very few treatment options one of which is overdenture. In this case report, a patient was treated with overlay removable partial denture for restoring the lost vertical dimension. This was provided as interim prosthesis. The follow up was done to observe the fulfillment of desired results. The clinical and laboratory procedure is described briefly. The treatment used for this case is cost effective and conservative solution for esthetic and functional rehabilitation. Since the material is acrylic resin, long term wear resistance is crucial for success of treatment. The rehabilitation would be fixed prosthesis with newly adjusted vertical dimension. DOI: http://dx.doi.org/10.3329/cdcj.v9i1.11835 City Dental College Journal Vol.9(1) 2012 28-31